Industrial Agriculture and Ape Conservation - Foundation, Arcus (Life Sciences, 2016)
This second volume in an important series examines the interface between ape conservation and industrial agriculture, presenting original research as well as topical case studies. It aims to influence debate, practice and policy for a broad range of policy makers, industry experts, decision makers, academics, researchers and NGOs. This title is also available as Open Access via Cambridge Books Online.